2023
DOI: 10.2196/42415
|View full text |Cite
|
Sign up to set email alerts
|

Stress Management Apps: Systematic Search and Multidimensional Assessment of Quality and Characteristics

Sarah Paganini,
Evelyn Meier,
Yannik Terhorst
et al.

Abstract: Background Chronic stress poses risks for physical and mental well-being. Stress management interventions have been shown to be effective, and stress management apps (SMAs) might help to transfer strategies into everyday life. Objective This review aims to provide a comprehensive overview of the quality and characteristics of SMAs to give potential users or health professionals a guideline when searching for SMAs in common app stores. … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(1 citation statement)
references
References 81 publications
0
1
0
Order By: Relevance
“…Previous studies in the literature have documented that mobile application utilization increased exponentially throughout the ongoing COVID-19 epidemic [31]. A study that conducted a search of the European Google Play Store and Apple App Store found that there were 121 stress management apps (SMAs) [32]. Web or mobile applications for cognitive interventions, such as Lumosity, are also becoming more widespread.…”
Section: Mobile Technology Application and Virtual Reality Nature Int...mentioning
confidence: 99%
“…Previous studies in the literature have documented that mobile application utilization increased exponentially throughout the ongoing COVID-19 epidemic [31]. A study that conducted a search of the European Google Play Store and Apple App Store found that there were 121 stress management apps (SMAs) [32]. Web or mobile applications for cognitive interventions, such as Lumosity, are also becoming more widespread.…”
Section: Mobile Technology Application and Virtual Reality Nature Int...mentioning
confidence: 99%